Flouting Maxim in “It’s Mine” Line Webtoon - Ni Wayan Nana Anggi Putri; I Gusti Ngurah Adi Rajistha (PRAGMATICA : Journal of Linguistics and Literature, 2026)
The title of this research is “Flouting Maxim in "It's Mine" Line Webtoon”. This research is aimed to describe kinds of flouting maxim and conversational implicature based on Grice’s theory. The data source used in this research is an e-comic on English Line Webtoon entitled "It's Mine". The data is collected from the utterances of the characters in the dialogues and analyzed based on the storyline and context of the conversation. The data were collected by downloading the application, reading the comic, and then collecting the data by taking a note which reflects the phenomena of maxim flouting, also identifying the conversational implicature of each kind of flouting maxim. The results of the research showed the four kinds of flouting maxims found in the Line Webtoon, there were 5 flouting maxims of quantity; 5 flouting maxims of quality; 5 flouting maxims of relation; and 3 flouting maxims of manner. Hence the total number of flouting maxims is 18. Furthermore, each kind of flouting maxim has two categories of conversational implicature, such as generalized conversational implicature and particularized conversational implicature.